2015
DOI: 10.4018/ijopcd.2015040101
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Style-Based Adaptive Learning System Architecture

Abstract: In the current study of learning process that show learners will take a different way and use different types of learning resources in order to learning better. Any many researchers also agree that learning materials must be able to meet the various learning styles of learners. Therefore, let learners can effective to improve their learning, for different learning styles of learners should be given different types of learning materials. In this paper the authors propose a learner's learning style-based adaptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…AccordingtoastudybyLiandYang(2016),Chinesestudents'learningstylehadnoinfluence on their concentration and learning; nevertheless, they concluded that "…appropriate mobile learningmaterialsshouldbedevelopedandusedtoeducatestudentsonthebasisoftheirrespective concentration,interest,andlearningstyles…"(p.922. ).Withtheevolutionofmediatechnologythere comesaneedtoprovidedifferenttypesoflearningresourcesandmaterials (Chin,Chu,&Huang, 2015).Thissituationposestwoproblems:1)providingthesameacademicmaterialforallthelearners, and2)dealingwiththecognitiveoverloadproducedbyanoverabundanceofnewinformation (Chin, Chu,&Huang,2015). Chin,Chu,andHuang(2015)concludedthatwhenlearningmaterialsare offeredinamannerconsistentwiththelearner'slearningstyle,learningwillbecomeeasier,more natural,andreducelearningtime,whichcouldleadtothemorerapidformationofappropriateschemas.…”
Section: Learning Stylesmentioning
confidence: 99%
“…AccordingtoastudybyLiandYang(2016),Chinesestudents'learningstylehadnoinfluence on their concentration and learning; nevertheless, they concluded that "…appropriate mobile learningmaterialsshouldbedevelopedandusedtoeducatestudentsonthebasisoftheirrespective concentration,interest,andlearningstyles…"(p.922. ).Withtheevolutionofmediatechnologythere comesaneedtoprovidedifferenttypesoflearningresourcesandmaterials (Chin,Chu,&Huang, 2015).Thissituationposestwoproblems:1)providingthesameacademicmaterialforallthelearners, and2)dealingwiththecognitiveoverloadproducedbyanoverabundanceofnewinformation (Chin, Chu,&Huang,2015). Chin,Chu,andHuang(2015)concludedthatwhenlearningmaterialsare offeredinamannerconsistentwiththelearner'slearningstyle,learningwillbecomeeasier,more natural,andreducelearningtime,whichcouldleadtothemorerapidformationofappropriateschemas.…”
Section: Learning Stylesmentioning
confidence: 99%
“…As new information technology continues to advance, instructional designers could design relevant digital learning that may provide different types of learning resources or materials for students (Chen, Chiu, & Huang, 2015). Teachers should adopt and integrate effective online teaching methods into online courses to help students achieve better learning performances.…”
Section: The 10th Titled Factors Of Participants and Blogs That Prementioning
confidence: 99%